LESI SERVIX PADA WANITA USIA SUBUR DALAM PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT - Bambang Sarwono (JURNAL KEBIDANAN, 2017)
Screening IVA inspection helpful to know that there are lesions on the cervix. The incidence of cervical cancer in Wonosobo 1.1% higher than the incidence in Central Java province and 1.5% higher than the incidence of cervical cancer in Indonesia. This research method using cross sectional analytic method correlational retrospective approach and supported by qualitative. Samples of all women of childbearing age who check the cervix with IVA method in Wonosobo district health center in 2013, as many as 1710 people The results of the bivariate statistical analysis using chi square p value = 0.043 with RP = 1,638 (CI 95% to the value range 1023 -2622). This means that there is a significant relationship between history kaknker in families with positive VIA test results. Cancer family history is a risk factor for cervical lesions WUS in Wonosobo regency. Conclusions history of cancer in families at risk of cervical lesions occur 1,831 times compared WUS patients with no history of cancer in the family. WUS age and the age of first sexual activity is a risk factor protective whereby 95% confidence interval for the number one in women of reproductive age